Nigral volumetric and microstructural measures in individuals with scans without evidence of dopaminergic deficit - Langley, Jason; Hwang, Kristy S.; Hu, Xiaoping P.; Huddleston, Daniel E. (Frontiers in Neuroscience, 2022)
Introduction: Striatal dopamine transporter imaging using 123I-ioflupane SPECT (DaTScan, GE) identifies 5-20% of newly diagnosed Parkinson’s disease (PD) subjects enrolling in clinical studies to have scans without evidence of dopaminergic deficit (SWEDD). These individuals meet diagnostic criteria for PD, but do not clinically progress as expected, and they are not believed to have neurodegenerative parkinsonism. Inclusion of SWEDD participants in PD biomarker studies or therapeutic trials may therefore cause them to fail. DaTScan can identify SWEDD individuals, but it is expensive and not widely available; an alternative imaging approach is needed. Here, we evaluate the use of neuromelanin-sensitive, iron-sensitive, and diffusion contrasts in substantia nigra pars compacta (SNpc) to differentiate SWEDD from PD individuals. Methods: Neuromelanin-sensitive, iron-sensitive, and diffusion imaging data for SWEDD, PD, and control subjects were downloaded from the Parkinson’s Progression Markers Initiative (PPMI) database. SNpc volume, SNpc iron (R2), and SNpc free water (FW) were measured for each participant. Results: Significantly smaller SNpc volume was seen in PD as compared to SWEDD (P<10-3) and control (P<10-3) subjects. SNpc FW was elevated in the PD group relative to controls (P=0.017). No group difference was observed in SNpc R2. Conclusion: In conclusion, nigral volume and FW in the SWEDD group were similar to that of controls, while a reduction in nigral volume and increased FW were observed in the PD group relative to SWEDD and control participants. These results suggest that these MRI measures should be explored as a cost-effective alternative to DaTScan for evaluation of the nigrostriatal system.